Los claroscuros del sexting: Argumentos para analizar una práctica controvertida - Arias, Valentina (2022)
Usually, discourses about sexting appear polarized: on the one hand, as a practice of sexual expression and empowerment for women, and on the other hand, as a risky exercise that needs to be controlled or discouraged. The aim of this research is to analyze certain features of sexting in young Argentine women, especially those characteristics that come into tension with both the celebrating and critical gazes. Drawing on in-depth interviews with women aged 18-25, we describe some of the tensions that occur when they sext, such as the sexual reobjectification of their bodies in a context of post-feminist sensibility, or the limits of consent in virtual sexual practices. However, singular uses and meanings also appeared, that cannot be subsumed to a disciplinary or patriarchal subjection of the body and sexuality. Thus, we propose a form of approach from a conjunctive logic, which allows us to understand these practices in all their complexity.